Unified transition to cooperative unmanned systems under Spatial Grasp paradigm - Sapaty, Peter S. (Discoveries in Agriculture and Food Sciences, 2014)
A novel philosophy, ideology, methodology, and supporting high-level networking technology will be revealed capable of guiding gradual transition to intelligent unmanned systems with a variety of important practical applications. The approach is based on a completely different type of high-level language capable of grasping top semantics of complex spatial operations in dynamic and unpredictable environments while shifting numerous technical details to effective automatic implementation. The language is based on holistic and gestalt principles rather than traditional multi-agent organizations, providing high integrity and super-summative features of the solutions described. Cooperative networked interpretation of the language in distributed systems and different parallel and distributed scenarios in it will be demonstrated that can be performed by any combination of manned and unmanned components under unified command and control provided by the technology described.